EFFECT OF SCARIFICATION TREATMENTS ON HARDSEEDEDNESS IN TWO WILD SPECIES OF CORCHORUS - KAK, ANJALI; GUPTA, VEENA; DEVI, CHITRA (Annals of Agricultural Research, 2014)
The effect of various scarification treatments on hardssedeness of two wild species of Corchrus was studied. Increased germination was recorded using acid scarification for 10 minutes and hot water treatment at 80 oC for 3 minutes and 5 minutes in C. tridens whereas concentrated acid treatment for 40 minutes in C. trilocularis. Subjecting seeds to dry heat was found ineffective in removing hardseededness.